Fenomena raynaud sekunder pada seorang penderita kanker kolon - I Gusti Agung Indra Adi Kusuma; Gede Kambayana (DiscoverSys Inc., 2020)
Introduction: Secondary Raynaud's phenomenon (RP) is a transient microvascular spasm associated with other etiologies with clinical features of triphasic manifestations. Malignancy is a rare cause of secondary RP. Case Report: A man, 46 years, came to Sanglah General Hospital with secondary RP and colorectal malignancy. Discoloration white at the distal digits of the right manus and digits 3-5 left and sometimes accompanied thick at the fingertips, involved proximal to the medial phalanges. Laboratory examination showed albumin 2.55 g / dL, globulin 2.12 g / dL, LDH 323 IU / L, CRP 6.5 mg / dL, CEA 5.83 ng / mL plain abdominal radiograph impression of thickening on the part of the wall and show colitis appearance, be suspected ileus in the upper left abdominal region. Base on histopathological examination, ascending colon presents well-differentiated adenocarcinoma, and abdominal CT shows liver metastases. Management of patients with secondary RP with lifestyle and pharmacological interventions and chemotherapy for colorectal adenocarcinoma as the underlying cause. Pharmacological therapy of RP with intraoral amlodipine Conclusion: Malignancy in this patient as a cause of RP and management is carried out to treat primary disease and Raynaud's Pendahuluan: Fenomena Raynaud (RP) sekunder merupakan vasokontriksi transien pada mikrovaskular dikaitkan dengan etiologi lain dengan gambaran manifestasi trifasik. Keganasan menjadi kausa yang jarang pada RP sekunder.Laporan Kasus: Seorang laki-laki, usia 46 tahun, datang ke RSUP Sanglah dengan RP sekunder dan keganasan kolorektal. Dengan pucat pada distal digiti manus dekstra dan digiti 3-5 sinistra dan disertai kadang tebal di ujung jari, meliputi proksimal sampai medial falang. Pemeriksaan laboratorium menunjukkan albumin 2,55 g/dL, dan globulin 2,12 g/dL, LDH 323 IU/L, CRP 6,5 mg/dL, CEA 5,83 ng/mL dengan foto polos abdomen kesan penebalan pada sebagian dinding usus menunjukkan suatu gambaran kolitis yang diduga ileus pada regio abdomen kiri atas, kolon asenden dengan gambaran well differentiated adenokarsinoma pada hasil biopsi histopatologi dan CT abdomen menunjukkan metastasis pada hepar. Penatalaksanaan pasien RP sekunder dengan intervensi gaya hidup dan farmakologis serta kemoterapi untuk adenokarsinoma kolorektal sebagai penyebab dasar. Terapi farmakologis RP dengan pemberian amlodipin intra oral.Simpulan: Kondisi keganasan pada pasien sebagai kausa dari RP dan tatalaksana pengobatan spesifik RP.